1988
DOI: 10.1111/j.1748-1716.1988.tb08500.x
|View full text |Cite
|
Sign up to set email alerts
|

Strength of two‐ and one‐leg extension in man

Abstract: Two- and one-leg extension strengths were compared in 155 female and male, untrained and trained (eight bicyclists, 38 weight-lifters) subjects and in a polio patient with almost no strength in one leg. On average two-leg strength was 82 +/- 1.3% (SE) of the sum of the strength of the right and left legs (leg-strength ratio) with no significant difference between the untrained and trained subjects. In the polio patient two-leg strength was lower than the strength of the strongest leg. A similar leg-strength ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 16 publications
3
55
0
1
Order By: Relevance
“…15, 17, 20-22, 24, 25, 27, 28, 30, 32, 33, 41) and has become known as the bilateral deficit (BLD). For example, a 7-25% reduction in bilateral force production compared with summed unilateral output has been reported for isometric knee extension and combined isometric hip and knee extension (17,22,33,34,37). Dynamic contractions also display this phenomenon (33,(39)(40)(41)(42)(43)(44)(45), and a similar effect has been found for the upper limbs, although the deficit is generally smaller compared with the lower limbs (for a review, see Ref.…”
mentioning
confidence: 76%
“…15, 17, 20-22, 24, 25, 27, 28, 30, 32, 33, 41) and has become known as the bilateral deficit (BLD). For example, a 7-25% reduction in bilateral force production compared with summed unilateral output has been reported for isometric knee extension and combined isometric hip and knee extension (17,22,33,34,37). Dynamic contractions also display this phenomenon (33,(39)(40)(41)(42)(43)(44)(45), and a similar effect has been found for the upper limbs, although the deficit is generally smaller compared with the lower limbs (for a review, see Ref.…”
mentioning
confidence: 76%
“…The decrease in bilateral force is not due to increased antagonist activity. 7,13 Bilateral deficit is influenced by training 14,15 but in order to reduce bilateral deficit the training must be bilateral training, and commensurate with the testing protocol. 16 The most often cited mechanism for bilateral deficit is a lesser activation of fast twitch motor units 2,13,17 but whether this originates due to inter-hemispheric inhibition, 18 or at other supraspinal levels, 16,19 or both, is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Secher et al 8 found bilateral deficit in multiarticular exercises as leg press (lower limb), but not for the bench press (upper limb/multiarticular) in a group of younger volunteers.…”
Section: Discussionmentioning
confidence: 96%
“…Such deficit has been studied through strength and electromyography, confirmed most of the times with the use of uniarticular exercises [3][4][5][6][7] being controversial concerning EMG and strength in multiarticular exercises for lower and upper extremities 3,8 .…”
Section: Introductionmentioning
confidence: 99%